1993
DOI: 10.1180/minmag.1993.057.387.05
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium highly anisometric crystals and whiskers of galena

Abstract: Unusual irregular galena crystals and whiskers were found in close proximity in some druse cavities from the Gradishtc hydrothcrmal lead-zinc deposit in the Madan ore district, Bulgaria. The following crystal forms were observed: (1) straight thin [110] whiskers and thicker needles; (2) kinked whiskers; (3) curvilinear whiskers; (4) complex tortuous whiskers composed of segments with varying directions--[ll0], [1(30], [211], (5) thicker irregular elongated crystals. Combinations of these forms occur also. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As will be shown in this study, acicular vesuvianite displays zonal growth, whereas whiskers are homogeneous. The appearance of natural whiskers depends on growth conditions and mechanism of crystal growth (Maleev 1971, Bonev 1993, Bonev et al 1985, Galuskin & Winiarski 1997. Whiskers of pyroxenes and amphiboles are well known, and their one-dimensional growth is generally attributed to polymerization of SiO 4 tetrahedra forming chains or bands (Maleev 1971, Galuskin & Mokhov 1991, Armbruster et al 2000c, 2002b.…”
Section: Background Informationmentioning
confidence: 99%
“…As will be shown in this study, acicular vesuvianite displays zonal growth, whereas whiskers are homogeneous. The appearance of natural whiskers depends on growth conditions and mechanism of crystal growth (Maleev 1971, Bonev 1993, Bonev et al 1985, Galuskin & Winiarski 1997. Whiskers of pyroxenes and amphiboles are well known, and their one-dimensional growth is generally attributed to polymerization of SiO 4 tetrahedra forming chains or bands (Maleev 1971, Galuskin & Mokhov 1991, Armbruster et al 2000c, 2002b.…”
Section: Background Informationmentioning
confidence: 99%
“…Meanwhile, the experiments clearly showed that the reaction temperature was increased by around 80°C abruptly (from 850 to 930°C) in a short time owing to the carbonisation of the surfactant NP-9. The increase in reaction temperature may produce a highly non-equilibrium condition and supersaturated solution [29], which can directly lead to the growth of whisker-like Mg 2 B 2 O 5 crystals. The growth mechanism of whisker-like Mg 2 B 2 O 5 crystals is similar to the growth process of fine needle-like galena skeletons from highly supersaturated solutions [29].…”
Section: Resultsmentioning
confidence: 99%
“…In their morphological characteristics the rounded galena pillars contrast with the highly anisometric needle-like crystals and whiskers formed in growth processes (Bonev, 1993). These growth forms are entirely bounded by smooth and striated crystal faces, and follow crystallographic directions determined by the existing faceting.…”
Section: Morphology and Orientation Of Pillarsmentioning
confidence: 96%
“…It is particularly surprising to find them in a highly symmetrical material such as hexoctahedral PbS. However, extremely anisometric crystals and whiskers of galena can arise under suitable hydrothermal conditions as non-equilibrium growth forms (Bonev, 1993).…”
Section: Introductionmentioning
confidence: 99%